Differential regulation of MYC expression by PKHD1/Pkhd1 in human and mouse kidneys: phenotypic implications for recessive polycystic kidney disease - Harafuji, Naoe; Yang, Chaozhe; Wu, Maoqing; Thiruvengadam, Girija; Gordish-Dressman, Heather; Thompson, R. Griffin; Bell, P. Darwin; Rosenberg, Avi Z.; Dafinger, Claudia; Liebau, Max C.; Bebok, Zsuzsanna; Caldovic, Ljubica; et al. (Frontiers in Cell and Developmental Biology, 2023)
Autosomal recessive polycystic kidney disease (ARPKD; MIM#263200) is a severe, hereditary, hepato-renal fibrocystic disorder that leads to early childhood morbidity and mortality. Typical forms of ARPKD are caused by pathogenic variants in the PKHD1 gene, which encodes the fibrocystin/polyductin (FPC) protein. MYC overexpression has been proposed as a driver of renal cystogenesis, but little is known about MYC expression in recessive PKD. In the current study, we provide the first evidence that MYC is overexpressed in kidneys from ARPKD patients and confirm that MYC is upregulated in cystic kidneys from cpk mutant mice. In contrast, renal MYC expression levels were not altered in several Pkhd1 mutant mice that lack a significant cystic kidney phenotype. We leveraged previous observations that the carboxy-terminus of mouse FPC (FPC-CTD) is proteolytically cleaved through Notch-like processing, translocates to the nucleus, and binds to double stranded DNA, to examine whether the FPC-CTD plays a role in regulating MYC/Myc transcription. Using immunofluorescence, reporter gene assays, and ChIP, we demonstrate that both human and mouse FPC-CTD can localize to the nucleus, bind to the MYC/Myc P1 promoter, and activate MYC/Myc expression. Interestingly, we observed species-specific differences in FPC-CTD intracellular trafficking. Furthermore, our informatic analyses revealed limited sequence identity of FPC-CTD across vertebrate phyla and database queries identified temporal differences in PKHD1/Pkhd1 and CYS1/Cys1 expression patterns in mouse and human kidneys. Given that cystin, the Cys1 gene product, is a negative regulator of Myc transcription, these temporal differences in gene expression could contribute to the relative renoprotection from cystogenesis in Pkhd1-deficient mice. Taken together, our findings provide new mechanistic insights into differential mFPC-CTD and hFPC-CTD regulation of MYC expression in renal epithelial cells, which may illuminate the basis for the phenotypic disparities between human patients with PKHD1 pathogenic variants and Pkhd1-mutant mice.